On the Fly: Recent Progress on Autophagy and Aging in Drosophila - Maruzs, Tamás; Simon-Vecsei, Zsófia; Kiss, Viktória; Csizmadia, Tamás; Juhász, Gábor (Frontiers in Cell and Developmental Biology, 2019)
Autophagy ensures the lysosome-mediated breakdown and recycling of self-material, as it not only degrades obsolete or damaged intracellular constituents but also provides building blocks for biosynthetic and energy producing reactions. Studies in animal models including Drosophila revealed that autophagy defects lead to the rapid decline of neuromuscular function, neurodegeneration, sensitivity to stress (such as starvation or oxidative damage), and stem cell loss. Of note, recently identified human Atg gene mutations cause similar symptoms including ataxia and mental retardation. Physiologically, autophagic degradation (flux) is known to decrease during aging, and this defect likely contributes to the development of such age-associated diseases. Many manipulations that extend lifespan (including dietary restriction, reduced TOR kinase signaling, exercise or treatment with various anti-aging substances) require autophagy for their beneficial effect on longevity, pointing to the key role of this housekeeping process. Importantly, genetic (eg. Atg8a overexpression in either neurons or muscle) or pharmacological (eg. feeding rapamycin or spermidine to animals) promotion of autophagy has been successfully used to extend lifespan in Drosophila, suggesting that this intracellular degradation pathway can rejuvenate cells and organisms. In this review, we highlight key discoveries and recent progress in understanding the relationship of autophagy and aging in Drosophila.